A case of probable interpersonal violence from the Early Neolithic site at Smilčić, Croatia. (10th February 2020) - Janković, Ivor; Marijanović, Brunislav; Čavka, Mislav; Carić, Mario; Novak, Mario
Abstract: Archaeological excavations at the Early/Middle Neolithic site at Smilčić‐Barica in 2016/2017 revealed skeletal remains of three people. Of particular interest is the skeleton from Grave 2, directly dated to 5616 and 5485 cal BCE, that is, to the Early Neolithic Impresso Pottery Culture. The skeleton was positioned on its left side, in a crouched position with bended knees and its right arm flexed at the elbow. Based on metric and morphological observations, the skeleton belongs to a young male, aged between 25 and 35 years. The most interesting feature is a penetrating trauma, probably caused by a projectile, located at intertrochanteric crest on the posterior proximal side on the left femur. A 15 × 4 × 3 mm lithic fragment is still embedded in the bone. Due to post‐mortem damage around the injury, it was not possible to establish possible signs of healing and/or inflammation. However, osteogenic reaction around the fragment is noted on computer tomography, indicating survival for a longer period. This is the earliest example of interpersonal violence recorded on the eastern Adriatic coast.